A Chiral Bipyrimidine-Bridged Dy2 SMM: A Comparative Experimental and Theoretical Study of the Correlation Between the Distortion of the DyO6N2 Coordination Sphere and the Anisotropy Barrier - Díaz-Ortega, Ismael F.; Herrera, Juan Manuel; Reyes Carmona, Álvaro; Galán-Mascarós, José Ramón; Dey, Sourav; Nojiri, Hiroyuki; Rajaraman, Gopalan; Colacio, Enrique (Frontiers in Chemistry, 2018)
Chiral bipyrimidine-bridged dinuclear LnIII complexes of general formula [(-bipym){((+)-tfac)3Ln}2] and [(-bipym){((-)-tfac)3Ln}2], have been prepared from the assembly of Ln(AcO)3·nH2O (LnIII = Dy, Gd), (+)/(−)-3-(trifluoroacetyl)camphor enantiopure ligands ((+)/(-)-Htfac) and bipyrimidine (bipym). The structure and chirality of these complexes have been supported by single-crystal X-Ray diffraction and circular dichroism. The study of the magnetic properties of the GdIII complexes revealed a very weak antiferromagnetic interaction between the GdIII ions through the bipyrimidine bridging ligand. Ab initio CASSCF calculations indicated that the ground Kramers doublet (KD) of both DyIII centers is almost purely axial with the anisotropy axis located close to the two tfac- ligands at opposite sides of each DyIII atom, which create an axial crystal field. In keeping with this, ac dynamic measurements indicated slow relaxation of the magnetization at zero field with Ueff = 55.1 K, a pre-exponential factor of o = 2.17·10-6 s and QTM = 8s. When an optimal dc field of 0.1 T is applied, QTM is quenched and Ueff increases to 75.9 K with τo= 6.16 × 10-7 s. The DyN2O8 coordination spheres and SMM properties of [(-bipym){((+)-tfac)3Ln}2] and their achiral [(Dy(β-diketonate)3)2(µ-bpym)] analogous have been compared and a magneto-structural correlation has been established, which has been supported by theoretical calculations. In contrast to the GdIII compounds, the magnetic exchange interaction between the DyIII ions has been calculated to be very weak and, generally, ferromagnetic in nature. Relaxation mechanisms for [(-bipym){((+)-tfac)3Ln}2] and previously reported analogous have been proposed from ab initio calculations. As the magnetic exchange interaction found to be very weak, the observed magnetization blockade in these systems are primarily dictated by the single ion anisotropy of DyIII ions.